Simplify (-1/8)^8 × (-1/8)^-3: Complete Exponent Operation

Question

Simplify the following problem:

(18)8(18)3=? (-\frac{1}{8})^8\cdot(-\frac{1}{8})^{-3}=?

Video Solution

Solution Steps

00:00 Solve the following problem
00:02 According to the laws of exponents, a number (A) raised to the power of (M)
00:05 multiplied by the same number (A) raised to the power of (N)
00:08 equals the number (A) raised to the power of (M+N)
00:12 Let's apply this to the question
00:15 Let's calculate the exponent
00:20 According to the laws of exponents, a fraction (A/B) raised to the power of (-N)
00:25 equals the reciprocal fraction (B/A) raised to the power of (N)
00:30 Let's apply this to the question
00:34 We obtain the number (-8) to the power of (-5)
00:43 This is the solution

Step-by-Step Solution

Apply the power law for multiplication between terms with identical bases:

aman=am+n a^m\cdot a^n=a^{m+n} We'll apply this law to the problem:

(18)8(18)3=(18)8+(3)=(18)83=(18)5 \big(-\frac{1}{8}\big)^8\cdot\big(-\frac{1}{8}\big)^{-3}=\big(-\frac{1}{8}\big)^{8+(-3)}=\big(-\frac{1}{8}\big)^{8-3}=\big(-\frac{1}{8}\big)^5

In the first stage we applied the above power law and in the following stages we simplified the expression in the exponent,

Let's continue and use the power law for power of terms in parentheses:

(xy)n=xnyn (x\cdot y)^n=x^n\cdot y^n

We'll apply this law to the expression that we obtained in the last stage:

(18)5=(118)5=(1)5(18)5=1(18)5=(18)5 \big(-\frac{1}{8}\big)^5=\big(-1\cdot\frac{1}{8}\big)^5=(-1)^5\cdot\big(\frac{1}{8}\big)^5=-1\cdot\big(\frac{1}{8}\big)^5=-\big(\frac{1}{8}\big)^5

In the first stage we presented the expression in parentheses as a multiplication between negative one and a positive number. In the next stage we applied the above power law and then simplified the expression we obtained whilst noting that negative one to an odd power will (always) give the result negative one.

Next we'll recall two additional power laws:

a. The negative power law:

an=1an a^{-n}=\frac{1}{a^n}

b. The power law for power of a power:

(am)n=amn (a^m)^n=a^{m\cdot n}

We'll continue and apply these two laws to the expression that we obtained in the last stage:

(18)5=(81)5=8(1)5=85 -\big(\frac{1}{8}\big)^5=-(8^{-1})^5=-8^{(-1)\cdot5}=-8^{-5}

In the first stage we presented the fraction inside the parentheses as a term with a negative power using the above power law for negative power mentioned in a. above. In the next stage we applied the power law for power of a power mentioned in b. above carefully, given that the term inside the parentheses has a negative power. We then simplified the expression in the exponent.

Let's summarize the solution :

(18)8(18)3=(18)5=(18)5=(81)5=85 \big(-\frac{1}{8}\big)^8\cdot\big(-\frac{1}{8}\big)^{-3}=\big(-\frac{1}{8}\big)^5=-\big(\frac{1}{8}\big)^5=-(8^{-1})^5=-8^{-5}

Therefore the correct answer is answer d.

Answer

85 -8^{-5}